PERSEPSI CALON AYAH TERHADAP PERAN JENDER ANAK - Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
Understanding of the concept of androgyny and gender -free parenting should be developed by the candidate 's father as one of the important aspect of life for the children they will have in the future. Androgin integrating gender roles gender roles usually done by women (feminine ) or male ( masculine ). Androgin individuals will behave according to the situation rather than be limited by cultural rules about men or women so that more adaptive in a variety of social conditions ( Unger Crawford , 2000). Therefore, research on the understanding of gender roles is necessary. This study uses incidental sampling technique, where as many as 34 subjects prospective father of the young adult age groups were asked to complete the MF Scale (Scale Masculine - Feminine) which has been adapted from the BSRI (Bem Sex Role Inventory) creation Bem (1974 ) for the category " girls " and " boy ". X2 test results indicate a difference in the perception of gender roles prospective father against son. Boys perceived masculine gender role while girls androgyn or feminine gender role. Parents should stimulate the development of insight knowledge of the child in a way to stimulate a more "rich" and diverse. Psychoeducation programs should focus on the importance of understanding personality types androgin for boys, while the scientific discussion on the topic of parenting and gender, including the implications of gender bias being applied in the development of adverse parenting girls and boys need to be frequently held. Keywords : gender roles, perceptions, future father.